ANALISIS PENERAPAN SISTEM ADMINITRASI PERPAJAKAN MODERN DI KANTOR PELAYANAN PAJAK PRATAMA PEKANBARU SENAPELAN - Ria Noviana; Parjiana M.Si (UIR Press, 2015)
This study aimed to determine an overview of the application of modern taxadministration system in the Kantor Pelayanan Pajak Pratama Pekanbaru Senapelan.Indicator pf the implementation of modern tax administration system used in cludesorganizational structure, improvement of business process through the usecommunication and information technologies, improvement of human resourcemanagement, and implementation of good governance. The type of research that islocated in the Kantor Pelayanan Pajak Pratama Pekanbaru Senapelan this is adescriptive survey, which prioritize the list of the questionnaire as a data collectiontool. Data collected with this tool used as raw material for analyzing the condition ofthe objectivity of the existence of empirical research purposes at the location of thestudied. Population and samples in this one leaders (section chief of service) and thetaxpayers whose number is infinite. Taxpayers who in this case are those who are doingthe tax administration in the Kantor Pelayanan Pajak Pratama Pekanbaru Senapelan.Large set of samples in this study were one leader and fifty taxpayers. The samplingtechnique used in determining the individual sample is census techniques for leadershipand sampling incidental techniques to the taxpayers. Type and data collectiontechniques used consisted of primary data were collected by using observation andinterview, as well as secondary data were collected using the techniques ofquestionnaires. While the data analysis technique used is to by using the tools frequencytable. This data analysis technique based researchers assed and conclude that theapplication of modern tax administration system in the Kantor Pelayanan PajakPratama Pekanbaru Senapelan the interval agreed assessment. The application ofmodern tax administration system in the Kantor Pelayanan Pajak Pratama PekanbaruSenapelan already well on the indicator in question.